Metal-induced changes in the early-life gut microbial composition and life-history traits in three insectivorous passerines - Rainio, Miia J.; Leino, Lyydia; Vesterinen, Eero; Sánchez Virosta, Pablo; Puigbò, Pere; Eeva, Tapio (Springer Nature, 2026)
Pollution-induced changes in gut microbiota may have serious effects on avian health and physiology. Particularly, early-life exposure to environmental pollutants may influence the gut microbiota development and microbiota-dependent physiological functions. We studied the associations of metal pollution with early-life microbial environment of wild passerines by exploring gut bacterial diversity and community composition in nestlings by 16S rRNA sequencing. Samples were collected from three common model species, great tits (Parus major), blue tits (Cyanistes caeruleus), and pied flycatchers (Ficedula hypoleuca) breeding near a copper-nickel smelter, an area with the highest rates of metal pollution in Finland. Responses of microbiota to pollution and microclimate were measured and connected to ecological measures (brood size, growth, fledging success) of nestling performance. The most abundant bacterial phyla across species were Firmicutes, Proteobacteria and Actinobacteria. Our results showed that the faecal microbial alpha diversity decreased with increasing brood size in great tits and blue tits, while in pied flycatchers the diversity increased with increasing nestling growth. However, alpha diversity did not differ between the polluted and control areas. The faecal microbial communities (beta diversity) differed between the species and study areas, and several bacterial orders were associated with metal concentrations, temperature, body mass, or fledging success. Differential abundance analyses showed species-specific differences in microbial abundances between polluted and control areas, e.g., Catellicoccus and Serratia showing elevated abundance within the polluted area. The results suggest that metal pollution may alter the early-life bacterial communities in small passerine species living in metal-polluted areas.